Acceptance and Commitment Therapy-Based Intervention to Manage Stigma toward Substance use Disorders - Joanna Gonçalves de Andrade Tostes; Pollyanna Santos da Silveira; Leonardo Fernandes Martins; Stephanie Knaak; Telmo Mota Ronzani (Estudos de Psicologia (Campinas))
Abstract Objective Stigma of health service professionals toward people with substance use disorders seriously compromises quality of care. A worldwide agenda points out how crucial it is to invest in evidence-based interventions to address stigma. This study aimed to describe the development process of an innovative intervention protocol to manage stigma based on Acceptance and Commitment Therapy. Method This is an empirical qualitative study. Phase 1: Guiding axes from evidence-based literature to define the active components. Phase 2: Protocol preliminary version and reporting based Template for Intervention Description and Replication guide. Phase 3: Expert judges to assess the first step of the content validation. Results We present 10 active components we achieved through a 12-hour face-to-face intervention, evaluated by expert judges. Conclusion This intervention is notable in terms of its coverage, accuracy, and suitability for health service professionals, and seems promising to be implemented for testing and replication.